The burden of neuropsychiatric disorders in patients living with HIV-1 treated with antiretroviral therapies—A perspective from US Medicaid data. (March 2022) - Chow, Wing; Hardy, Hélène; Song, Ji; Connolly, Nancy; Wu, Bingcao
Background: People with human immunodeficiency virus (HIV)-1 face challenges with treatment adherence for various reasons, including consideration of neuropsychiatric disorders and neuropsychiatric adverse reactions associated with antiretroviral therapy (ART). Methods: A retrospective cohort study was conducted using administrative claims data from the IBM MarketScan ® Multi-State Medicaid Database (1/1/2014–12/31/2017). Adults (≥18 years) diagnosed with HIV-1 and newly initiated on antiretroviral therapy with continuous health plan enrollment were included. Primary outcome was the 6-month period prevalence of neuropsychiatric events (NPEs) of interest after ART initiation. Results: Among 1971 newly treated patients included in the study, mean age (standard deviation [SD]) was 38.5 (12.7) years, and 41.4% were female. During the 6 months after ART initiation, 51.4% of patients had a claim for ≥1 NPE versus 30.3% of matched patients without HIV. Among newly treated patients, the most common (≥10%) NPE claims were for depression (42.2%), anxiety (15.8%), headache (11.9%), and bipolar/manic depression (10.1%). Also in this group, the mean (SD) total all-cause healthcare cost during the 6-month post-ART initiation was $16, 632 ($33, 928), of which $2914 ($18, 233) was NPE-related. Conclusions: In summary, in this Medicaid study of people newly initiated on ART, there was a high prevalence of NPEs, and incremental NPE-associated costs were considerable.